2022
DOI: 10.3390/ani12172207
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Spatial Restriction Generates Deferred Limited Space Use in a Zoo-Housed Chimpanzee Group

Abstract: Background: Appropriate space is considered paramount for good captive animal welfare. There has been a concerted effort by captive institutions, particularly zoos, to provide captive animals with relatively large, naturalistic enclosures which havehad demonstrated welfare benefits for animals. However, post-occupancy assessments of these enclosures tend to focus on short-term welfare-centredbehavioural effects or human perceptions of the enclosures and their effects and seldom consider spaceuse. We examined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 105 publications
0
0
1
Order By: Relevance
“…This differs from some previous studies of zoo-living apes who were reluctant to utilize new outdoor enclosure space [ 15 , 49 ]. However, Ross [ 15 ] determined that chimpanzees and gorillas both used their outdoor areas, with chimpanzees using the area for about a third of the observation time, while Bloomsmith [ 50 ] found that research facility chimpanzees spent 45% of their time outside.…”
Section: Discussioncontrasting
confidence: 90%
“…This differs from some previous studies of zoo-living apes who were reluctant to utilize new outdoor enclosure space [ 15 , 49 ]. However, Ross [ 15 ] determined that chimpanzees and gorillas both used their outdoor areas, with chimpanzees using the area for about a third of the observation time, while Bloomsmith [ 50 ] found that research facility chimpanzees spent 45% of their time outside.…”
Section: Discussioncontrasting
confidence: 90%